Activity in the Arbuscular Mycorrhizal Hyphosphere Warning Neighbouring Plants - Cabral, Carmina; Wollenweber, Bernd; António, Carla; Ravnskov, Sabine (Frontiers in Plant Science, 2019)
Pathogen infections of the phyllosphere have been investigated in detail, however, the changes induced by these infections on the arbuscular mycorrhizal hyphosphere, and the consequent signalling to the neighbouring plants have been scarcely investigated. Here, our objectives were to document that B.fabae infection of connected Vicia faba plants resulted in changes in the metabolism and microbial community of the hyphosphere, confirming the induction of plant defence in connected plants through gene-expression evaluations. Infected plants were challenged with B. fabae for 72 hours. Changes in gene-expression of pathogenesis-related proteins 1,2 and 5 (PR1, PR2,PR5) of both infected- and non-infected plants were analysed, to confirm signalling through the hyphosphere. The primary metabolic profiles and changes in the level of microbiota in the hyphosphere were assessed. Changes in expression of PR1, PR2 and PR5 genes occurred in the neighbouring plants 24 hours after infection. Mannitol levels decreased in presence of AMF. A decrease in the level of actinobacteria in the hyphosphere of infected plants was detected. We conclude that B.fabae infection induced a signalling event through the AM hyphosphere, confirmed by changes in defence gene-expression in non-infected neighbouring plants, influenced primary metabolic activity of-, and affected the microbial composition within-, the AM hyphosphere.